Green chemistry and computational chemistry : shared lessons in sustainability - Mammino, Liliana (Advances in green and sustainable chemistry., 2022)
Green chemistry already draws on many techniques and approaches developed by theoretical chemists, whilst simultaneously revealing a whole range of interesting new challenges for theoretical chemists to explore. Highlighting how work at the intersection of these fields has already produced beneficial results, Green Chemistry and Computational Chemistry: Shared Lessons in Sustainability is a practical, informative guide to combining green and theoretical chemistry principles and approaches in the development of more sustainable practices. Beginning with an introduction to both theoretical chemistry and green chemistry, the book goes on to explore current approaches being taken by theoretical chemists to address green and sustainable chemistry issues, before moving on to highlight ways in which green chemists are employing the knowledge and techniques of theoretical chemistry to help in developing greener processes. The future possibilities for theoretical chemistry in addressing sustainability issues are discussed, before a selection of case studies provides good insight into how these interactions and approaches have been successfully used in practice.--